Blood glucose and lactate kinetics during an incremental running test in endurance runners - Nakamura, K.; Sengoku, Y.; Ogata, H.; Watanabe, K.; Shirai,Y.; Nabekura, Y. (International Journal of Sport & Health Science, 2016)
Aim: We examined the difference in blood glucose and lactate kinetics between highly and moderately trained runners during an incremental running test, and to examine the relationship between GT and LT in different training states. Methods: Eight highly trained (25.9 ± 5.6 years, 167.6 ± 5.2 cm, 57.5 ± 6.0 kg) and eight moderately trained (23.8 ± 3.7 years, 173.6 ± 3.8 cm, 62.4 ± 4.6 kg) male runners performed the incremental running test. Each stage of the test consisted of running for 4 min on a treadmill. The velocity was increased by 0.6 km·h-1·stage-1 until exhaustion. Blood glucose and lactate were measured after each stage, and GT and LT were determined using the log-log method. Results: During the incremental running test, blood lactate increased significantly in both groups, whereas blood glucose increased significantly only in highly trained runners. In highly trained runners, LT and GT did not differ significantly (15.2 ± 1.0 and 15.7 ± 1.3 km·h-1, respectively; p = 0.08), but were significantly correlated (r = 0.906, p <0.01). In moderately trained runners, however, LT was significantly lower than GT (12.1 ± 0.8 and 13.7 ± 1.6 km·h-1, respectively; p = 0.02), and no significant correlation was observed between LT and GT (r = 0.596, p = 0.16). Conclusions: The relationship between blood glucose and lactate kinetics differs according to training state, so that the relationship of blood glucose and lactate kinetics and appearance pattern of GT reflects a different exercise capacity than that of LT.